Global marine insurance premiums and the maritime industry - Oğuz, Hatice Selin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
Maritime transportation and insurance have always been very important two industries for the developments in trade. Many studies have been conducted to analyze the relationship between these industries and global economic indicators. Results obtained from these researches supported the strong connection between the global economic indicators and these two industries. Both maritime and insurance industries are found to follow a cyclical pattern with recurrent upward and downward movements. Many different hypotheses exist about the reason for these cycles. With this background, this thesis aims to reveal cyclical movements in global marine insurance premiums and maritime freight markets, then analyze the relationship between them. With this purpose, three hypotheses, which suggest that maritime freight markets follow a cyclical pattern, marine insurance premiums follow a cyclical pattern and these cycles are positively synchronized, are structured. To test these hypotheses, global marine hull insurance premiums, Baltic Dry Index values, and world merchant fleet volume data for 23 years between 1996 and 2018 is employed. The findings of the study support the cyclical movements in both industries. Cycles in marine insurance and maritime freight markets are found to be in a positive relationship. Unit hull insurance premium cycles have matched BDI cycles with a lag of years. Both hull insurance premiums and BDI showed a common cycle length of 16 years.
Keywords: Insurance, Marine.; Maritime law.